Design considerations and recommendations for the development of children therapeutic garden in Malaysian hospitals - Said, Ismail (2002)
The planning and designing of outdoor spaces in assisting the healing process of children in the hospital environment is new but full of prospect in health service sector in Malaysia. Experiencing with biotic, physical and climatic factors in the natural environment would nurture ill children through provision of space to play and get fascinated. Through passive and /or active participations with the garden elements, the children are able to get away from the confinement of ward conditions and routines of medical treatments. With proper design and implementation, the hospital outdoor spaces can be made into therapeutic platforms for the children to play, rest and socialise. The design must turn the place into a respite where the childrenâ€™s body and mind are engaged into a structured setting. Here they can experience diversity of forms, colours, shapes of landscape elements and dynamism of climatic factors, namely, light, wind and rain. All their senses can be stimulated by the garden environment that would lead to fascination and reduction of stress. Stress reduction is a crucial step in recuperation process that would result in several positive physiological outcomes including lower blood pressure, reduced muscle tension, and lower skin conductance. Furthermore, patients experiencing reduction of stress level would also display some psychological responses. In children, the responses are known as psychological peacefulness and adjustments that include less crying, more cooperation and more obedient toward clinical treatments given by caregivers of the hospitals. The effects of garden towards ill children treated in hospitals is described in depth in a research RMC 72338 Universiti Teknologi Malaysia report, â€œStudy on the Effectiveness of Therapeutic Garden as a Platform to Recuperate Ill Children in the Nucleus Hospital Environmentâ€ and later summarised in an article, â€œGarden as an Environmental Intervention in Healing Process of Hospitalised Childrenâ€. 1 Therefore, these design considerations and recommendations for the development of children therapeutic gardens are derived from the research done by Research Management Centre, Universiti Teknologi Malaysia from December 2000 to November 2002. The objectives of submission of these texts are (1) to share the research findings with Jabatan Landskap Negara for the development of therapy gardens in healthcare facilities, and (2) to call upon Jabatan Landskap Negara to finance Universiti Teknologi Malaysia to conduct more studies on therapeutic landscapes, including healing gardens for orthopaedics, Alzheimer, and terminally-ill (chronic) patients in hospital environment. Currently, UTM is making a link with the Department of Pediatrics, Universiti Sains Malaysia to jointly conduct this type of research.